Soteriology and the Sinicization of Christianit - TANG, Paul Honglin (Journal of Research for Christianity in China (JRCC), 2022)
Due to the exclusionary stance of soteriology, many Christians’ lives are divided into the holy and the secular. By analyzing three common positions of soteriology (exclusivism, inclusivism, and pluralism), this article shows that salvation is entirely possible outside Christianity, or among non-believers. In addition, the article also reflects on the gospel or salvation in light of Scripture, maintaining that the core of the good news is God himself, or the kingdom of God. To be saved is to enter the kingdom of God, but the kingdom of God lies not in the future, rather, the rule of God sets in the present. Therefore, the life of believers should be centered on the kingdom of God, and live beyond the life of the transcendent kingdom in the moment. Further, it is the life of obeying the Lord and managing the earth. The faith-centered practice not only helps to break down the barriers between believers and non-believers, but also necessary to build a harmonious China and thus further deepen the sinicization of Christianity.
Keywords: exclusivism, inclusivism, kingdom of God, pluralism, sinicization of Christianity